Functional Assessment of Coronary Artery Disease Using Whole-Heart Dynamic Computed Tomography Perfusion - Hubbard, Logan (Circ Cardiovasc Imaging, 2016)
BACKGROUND: Computerized tomography (CT) angiography is an important tool for evaluation of coronary artery disease (CAD), but often correlates poorly with myocardial ischemia. Current dynamic CT perfusion techniques can assess ischemia, but have limited accuracy and deliver high radiation dose. Therefore, an accurate, low-dose, dynamic CT perfusion technique is needed. METHODS AND RESULTS: A total of 20 contrast enhanced CT volume scans were acquired in 5 swine (40 ± 10 kg) to generate CT angiography and perfusion images. Varying degrees of stenosis were induced using a balloon catheter in the proximal left anterior descending (LAD) coronary artery and a pressure wire was used for reference fractional flow reserve (FFR) measurement. Perfusion measurements were made with only two volume scans using a new first-pass analysis (FPA) technique and with 20 volume scans using an existing maximum slope model (MSM) technique. Perfusion (P) and FFR measurements were related by P(FPA) = 1.01 FFR − 0.03 (R(2) = 0.85) and P(MSM) = 1.03 FFR − 0.03 (R(2) = 0.80) for FPA and MSM techniques, respectively. Additionally, the effective radiation doses were calculated to be 2.64 and 26.4 mSv for FPA and MSM techniques, respectively. CONCLUSIONS: A new FPA-based dynamic CT perfusion technique was validated in a swine animal model. The results indicate that the FPA technique can potentially be used for improved anatomical and functional assessment of CAD at a relatively low radiation dose.